Entrepreneurial Attitudes and Skills Internalization of Chinese Students’ - Jumardi Budiman (Jurnal Pendidikan Ekonomi Dan Bisnis (JPEB), 2020)
This study attempts to know about the process of internalization attitudes and skill of entrepreneurship to their students chinese. Object this study were chosen based on stereotype and its phenomena developing in the community west Kalimantan that of the Chinese must be traders. Methods used are qualitative to technique data collection using interviews and observation. Respondents this research is the student will Emmanuel Pontianak of Chinese ethnic and came from families entrepreneurs. Data analysis techniques used that is the reduction, data presentation of data and the withdrawal of conclusion. The result showed that the process internalization attitudes and entrepreneurship skills students derived from the informal education of the community, community school, and their peers. The business management internalization attitudes and skills to their students covering thriftiness, productive and orientation independent, able to make decisions and, bear the consequences not easily discouraged, and finish the first new demanding the right